Environmental Education in Initial Training: Effects of a Physical Activities and Sports in the Natural Environment Program for Sustainable Development - Santos-Pastor, M. Luisa; Ruiz-Montero, Pedro Jesús; Chiva-Bartoll, Oscar; Baena-Extremera, Antonio; Martínez-Muñoz, L. Fernando (Frontiers in Psychology, 2022)
Training for sustainable development is an educational challenge of prime importance. Physical activity and sports in natural environments provide training committed to sustainability and environmental education. The objective of this study was to assess the effects of an undergraduate training program in Physical Activities and Sports in Natural Environments concerned with sustainable development. A total of 113 students from the Autonomous University of Madrid (Spain) who are studying a Bachelor’s Degree in Physical Activity and Sports Sciences and a Master’s Degree in Teacher Training for Secondary Education and High School (specializing in Physical Education) were involved. Specifically, we aimed to assess the impact of this training program on three dimensions related to Environmental Education (knowledge, behaviors, and attitudes). Its effect was also examined bearing in mind students’ sex, age and educational profile (sportive and educational). Mixed-methods were used: for the quantitative approach, data were collected with the Environmental Attitude in Physical Activities in Natural Environments validated scale; for the qualitative approach individual reflective diaries completed by students that attended the program were analyzed. The results show positive effects on the students regarding the three dimensions of Environmental Education, for both the sportive and educational training profiles. The quantitative results do not present significant differences concerning the gender variable, although the qualitative information shows that female students perceived a greater environmental sensitivity during their practices. Regarding the age variable, significant differences are found in the youngest students with an educational profile. To conclude, the study ratifies that the program carried out generated improvements in terms of knowledge, behaviors and attitudes toward the environment and sustainable development. Future research should use larger samples and consider other variables related to education for sustainability.